Stigma as 'othering' among Christian theology students in South Africa : original article - Breda, Adrian D. Van (SAHARA : Journal of Social Aspects of HIV / AIDS Research Alliance, 2012)
HIV is a health and developmental crisis that has profoundly challenged the Christian church in sub-Saharan Africa. Responding to stigma and prejudice against HIV and people living with HIV and AIDS has been a major concern of theologians and Christian leaders. However, Christians themselves and the church as a community are equally prone to stigma and prejudice. The author contends that this stigma is grounded in the dynamic of 'othering', which, among Christians, takes on religious or theological overtones. Drawing on qualitative data from theology students in South Africa, the paper assembles a model of AIDS stigma as othering. The central story or axis of the model is the dynamic of othering, comprising three themes, viz. lack of empathic contact, disconnection, and distancing. There are three main dynamics that appear to contribute to or feed into othering, viz. emotions related to sexuality and HIV, theology of health and judgement, and contextualised knowledge of HIV. Finally, the model presents two primary results of othering, viz. disengagement from HIV through passivity and hopelessness, and prejudice against those living with HIV. The paper endeavours to reveal the possible biblical roots of AIDS stigma. Through this, the deep violence embedded in such stigma is exposed and contrasted with a theology of inclusiveness and engagement. Le Virus d'Immunodéficience Humain (VIH) est un problème de santé et de développement qui a profondément remis en question l'église chrétienne en Afrique sub-saharienne. Une préoccupation majeure des théologiens et des leaders religieux était d'apporter une réponse á la stigmatisation et aux préjugés á l'égard du VIH/SIDA et des personnes vivant avec le VIH. Cependant, les chrétiens eux-mêmes et l'église, en tant que communauté, sont également enclins á la stigmatisation et aux préjugés. L'auteur soutient que cette stigmatisation est ancrée dans la dynamique de differentiation or « othering », qui, parmi les chrétiens, prend des références religieuses ou théologiques. S'appuyant sur des données qualitatives provenant des étudiants en théologie en Afrique du Sud, le papier assemble un modèle de stigmatisation liée au SIDA comme differentiation or « othering ». Le principal axe du modèle est la dynamique de differentiation or « othering », comprenant trois thèmes, á savoir: l'absence de contact empathique, la déconnexion et de distanciation ou éloignement. Il y a trois principales dynamiques qui semblent contribuer á nourrir de differentiation or « othering », á savoir : les émotions liées á la sexualité et au VIH, la théologie de la santé et du jugement, et la connaissance contextualisée du VIH. Enfin, le modèle présente deux résultats primaires de differentiation or « othering », á savoir: désengagement vis-á-vis du VIH/SIDA par la passivité, le désespoir et les préjugés envers les personnes vivant avec le VIH. Le papier s'efforce de révéler les racines bibliques de possible stigmatisation liée au SIDA. Grâce á cela, la violence profonde incorporée dans cette stigmatisation est exposée et contrastée avec une théologie de l'inclusivité et de l'engagement.
Free